MENINGKATKAN KEMAMPUAN MENGENAL WARNA MELALUI MEDIA LEGO PADA ANAK USIA 4-5 TAHUN DI TK AN-NUUR BAGAN BATU KABUPATEN ROKAN HILIR - Nurlela Nurlela; Wusono Indarto; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrak : This research to do to understand student ability to colour identify for the student 4 – 5 years old in TK An-Nuur Bagan Batu Regency Rokan Hilir. This plan 15 use to achieve purpose class research with two cycle : First cycle, consist of three times meeting data accumulation technique by observation with descriptive analysis. The result of the research show the rescarch that consist from two cycle get increase, it’s happen before giving a treatment for the first cycle 31,5% the creasing for first cycle 44,4%. And in creasing before first cycle to second cycle 89,90%.Keywords: understanding colour, logo media